AMDAR y PCR-extra-rápida para la identificación de la tortuga cabezona Caretta caretta (Testudines: Cheloniidae) utilizando el gen mitocondrial citocromo c oxidasa I (COI) (2013)
We molecularly identified the loggerhead turtle Caretta caretta using high-speed PCR amplification and restriction analysis of mitochondrial DNA. We isolated the DNA from blood from juvenile C. caretta from Don Diego beach (Magdalena; n=4), in Islas Del Rosario (Bolívar; n=2) in the Colombian Caribbean. By using high-speed PCR amplification of mitochondrial cytochrome c oxidase I (COI), we reduced reaction by one third and obtained fragments of 650 base pairs. We analyzed the amplified IOC product using enzymes HindIII, HpyCH4III and MseI and generated an electrophoretic profile, which compared in silico to other sea turtle species sequences, revealed the loggerhead’s specific pattern. We found similarity between 97-99% with C. caretta in five of the BLAST analyzed nucleotide sequences and 92% in another. We generated a bar code for the sampled turtle information and sequences and stored them in the BOLD database. The methodology described for the identification of C. caretta is a fast and inexpensive procedure that minimizes time and improves PCR specificity.